135 Treating low-risk ductal carcinoma in situ (DCIS)... or not? Qualitative study of patient perspectives. (8th June 2022) - Hersch, Jolyn; Nickel, Brooke; Dixon, Ann; Houssami, Nehmat; Saunders, Christobel; Jansen, Jesse; Rutherford, Claudia; Barratt, Alexandra; Spillane, Andrew; Wylie, Liz; Stuart, Kirsty; Robertson, Geraldine; et al.
Abstract : Objectives: DCIS is a breast malignancy contained within the milk ducts. Prognostic uncertainty means discussing DCIS and its treatment are challenging. Recognition that some DCIS lesions might remain indolent for many years has led to concern about overtreatment, with international clinical trials underway assessing the safety of active monitoring for low-risk DCIS. We aimed to explore women's experiences of diagnosis and treatment of low-risk DCIS and their views about potential future management options. Method: Participants were 30 women aged 50–74 who had been diagnosed with low- or intermediate-grade DCIS through the Western Australian breast screening program and were 1.5 to 3 years post-diagnosis. We conducted qualitative semi-structured interviews by telephone. Topics included patients' experiences of diagnosis, decision making, treatment and recovery. We included a short hypothetical vignette exploring responses to a potential future option of active monitoring for DCIS. Interviews were audio-recorded, transcribed and analysed thematically. Results: Very few patients had heard of DCIS before diagnosis, and levels of understanding varied. All patients followed recommendations to undergo surgery; most felt anxious to be treated as soon as possible. Although patients were mostly satisfied with their care, some felt insufficiently supported or prepared, or questioned whether they should have had more or less aggressive treatment. Many were concerned their condition might recur or spread later. Few could countenance the idea of monitoring DCIS rather than removing it immediately. Conclusions: Patients newly diagnosed with DCIS are typically unfamiliar with the condition. Confusion and misunderstandings may compound patient distress and make it difficult to consider less intensive therapy. Although de-escalating treatment where possible was welcome to some, many participants felt uncomfortable with the suggestion that some future patients might undergo monitoring instead of immediate surgery. Optimising patient outcomes will require continued attention to effective clinical communication, shared decision making, and ongoing psychosocial support.